Second M3 muscarinic receptor binding site contributes to bronchoprotection by tiotropium. (2nd July 2019) - Kistemaker, Loes E.M.; Elzinga, Carolina R.S.; Tautermann, Christofer S.; Pieper, Michael P.; Seeliger, Daniel; Alikhil, Suraya; Schmidt, Martina; Meurs, Herman; Gosens, Reinoud
Abstract : Background and Purpose: The bronchodilator tiotropium binds not only to its main binding site on the M3 muscarinic receptor but also to an allosteric site. Here, we have investigated the functional relevance of this allosteric binding and the potential contribution of this behaviour to interactions with long‐acting β‐adrenoceptor agonists, as combination therapy with anticholinergic agents and β‐adrenoceptor agonists improves lung function in chronic obstructive pulmonary disease. Experimental Approach: ACh, tiotropium, and atropine binding to M3 receptors were modelled using molecular dynamics simulations. Contractions of bovine and human tracheal smooth muscle strips were studied. Key Results: Molecular dynamics simulation revealed extracellular vestibule binding of tiotropium, and not atropine, to M3 receptors as a secondary low affinity binding site, preventing ACh entry into the orthosteric binding pocket. This resulted in a low (allosteric binding) and high (orthosteric binding) functional affinity of tiotropium in protecting against methacholine‐induced contractions of airway smooth muscle, which was not observed for atropine and glycopyrrolate. Moreover, antagonism by tiotropium was insurmountable in nature. This behaviour facilitated functional interactions of tiotropium with the β‐agonist olodaterol, which synergistically enhanced bronchoprotective effects of tiotropium. This was not seen for glycopyrrolate and olodaterol or indacaterol but was mimicked by the interaction of tiotropium and forskolin, indicating no direct β‐adrenoceptor–M3 receptor crosstalk in this effect. Conclusions and Implications: We propose that tiotropium has two binding sites at the M3 receptor that prevent ACh action, which, together with slow dissociation kinetics, may contribute to insurmountable antagonism and enhanced functional interactions with β‐adrenoceptor agonists.